EMS: E-Merchant System - Kuan, Jiun Ying; Noryusliza Abdullah (Applied Information Technology And Computer Science, 2023)
EMS: E-Merchant System is a web-based system that allows merchants who do not have their own digital service system yet to use this developed system to own their ecommerce website by publishing their business online. The target users of this developed system are merchants and merchant customers. Some merchants have been slow to adopt digital services due to the cost of development and maintenance, lack of knowledge about digital management, and fear of negative impact on their original business. Therefore, this project is proposed to be developed. The Bootstrap framework, HTML, CSS, JavaScript, PHP and MySQL are used to develop the system. The waterfall model is chosen as the methodology. In the developed system, there are two types of users, namely merchants and customers. Through this developed system, merchants can own their own digital service system without spending too much time and money.